Rancangan Kontrol dan Monitoring Constant Current Regulator (CCR) pada Precision Approach Path Indicator (PAPI) Menggunakan Android Berbasis Arduino di Bandar Udara Internasional Lombok - Kustori Kustori; Zuris Nur Faiza Ningrum (Jurnal Penelitian)
Constant Current Regulator is a power supply used in the world of aviation for the provision of electric power in airport lighting systems. The electrical power supplied to the airport lighting lamp is maintained to provide power with constant current. It is intended that the runway lights, especially PAPI, has lighting in certain light brightness / intensity that we want according to the specified taping. At this time, CCR in Lombok International Airport has been using SCADA. Unfortunately for controlling and monitoring CCR on a runway lights especially PAPI can only be done in the control room, so engineers had to stand by in the control room. By given this design, android is expected to replace the SCADA that can be accessed remotely, no matter where technicians are located. Moreover, when the state requires you to change the CCR step, the technician can control CCR through android system in technician`s smartphone once monitor the CCR output current without having to stand by in the control room.